Philosophy, the World and Man: A Global Conception - Chatalian, G. (Obafemi Awolowo University Press, 2013)
This lecture has a twofold positive-constructive purpose and a twofold negative-destructive purpose. On the positive side, it attempts, first, to determine the nature of philosophy, and second to indicate the value for the human race in general of philosophy so conceived: something which is, I believe, very inadequately understood not only by the general public and by the general academic or intellectual community (not only in Africa but throughout the world), but also and most ironically by the community of philosophers themselves. On the negative side it attempts to justify the judgement that two groups of thinkers universally regarded as philosophers are not philosophers at all: the first group being the earliest of the so-called philosophers in Western history,' the ancient Greek thinkers of the sixth century B.C. known as the Milesians, and the second group (far more numerous and far more influential) being the latest of the so-called philosophers in Western history-the European thinkers of the twentieth century A.D. known generally as the Analytic Philosophers. In the second, third and fourth parts of the lecture I shall attempt to justify the negative judgements. Throughout, I shall attempt to justify the positive, constructive theses, and in the final part to state them and their implications more fully.